Un cas extrême de réduction des inégalités scolaires au Ceará (Brésil). Stratégie et efficience de la politique mise en œuvre - Maíra Mamede; Vanda Mendes Ribeiro; Sylvain Broccolichi; Maria do Carmo Meirelles Toledo Cruz (Les éditions de la Maison des sciences de l'Homme, 2021)
For the past 20 years, numerous evaluations and data compilations have provided comparative information on education systems and their results in terms of student achievement. It can be seen that while raising and equalizing student achievement is a recurrent objective of educational policies, progress in this direction is often limited, or even non-existent. Hence the interest in the significant progress observed over more than ten years in a Brazilian state where two of the authors of our article conducted research since 2005, shortly before the systemic strategy tested in one city was extended in stages to the rest of Ceará. The ongoing research has already identified several points of vigilance involved in the strategy: objectifying and analyzing precisely the failures and inequalities to be reduced, developing the tools, cooperation and power to act of the actors concerned, and continuously adjusting the evaluations and useful training according to the feedback from the field.